Burkitt-Type Acute Lymphoblastic Leukemia With Precursor B-Cell Immunophenotype and Partial Tetrasomy of 1q: A Case Report. Issue 10 (March 2016) - Sato, Yuya; Kurosawa, Hidemitsu; Fukushima, Keitaro; Okuya, Mayuko; Arisaka, Osamu
Abstract : Abstract: Burkitt-type acute lymphoblastic leukemia (B-ALL) is thought as a variant of Burkitt lymphoma/leukemia and derived from mature B-cell lymphoblast. B-ALL was developed in a 10-year-old girl. Two characteristics were apparent in this case. First, the lymphoblastic cells were positive for CD10, CD19, CD20, and CD22, but negative for terminal deoxynucleotidyl transferase and surface immunoglobulins, indicating a B-cell immunophenotype. The detection of t(8;14)(q24;q32) with a chromosomal analysis is required for a diagnosis of B-ALL. Second, der(1)(pter → q32.1::q32.1 → q21.1::q11 → qter) was detected, in which 1q21.1 to 1q32.1 was inverted and inserted. Finally, partial tetrasomy of 1q was also present. Because B-ALL with abnormal chromosome 1 has been reported poor outcome, the usual chemotherapy for stage 4 Burkitt lymphoma with added rituximab was administered for our patient. We report B-ALL with precursor B-cell immunophenotype and interesting partial tetrasomy of 1q.